PENGARUH STRUKTUR MODAL TERHADAP KINERJA KEUANGAN DENGAN GOOD CORPORATE GOVERNANCE SEBAGAI PEMODERASI SEBELUM DAN SESUDAH PANDEMI COVID-19 - Ghofar, Abdul; Nabiilah, Adinda Shafaa Nur (Jurnal Manajemen, Ekonomi dan Akutansi (JUMEA), 2025)
Amid tight competition and difficult economic conditions during the pandemic, making decisions about capital structure is important to sustain the business and avoid bankruptcy. Good Corporate Governance (GCG) is also considered an important component in the business decision-making process. As such, this study aims to examine the effect of capital structure on the financial performance of information technology companies listed on the Indonesia Stock Exchange (IDX) between 2018 and 2022, considering GCG as a moderating variable and comparing the effect before and after the COVID-19 pandemic. The research method is qualitative-correlational, and a purposive sampling technique is used to achieve the research aim. The results of the quantitative descriptive analysis exhibit that capital structure affects financial performance in the overall period and the period after the Covid-19 pandemic, but has no effect in the period before the Covid-19 pandemic. GCG moderation results show that GCG does not strengthen the effect of capital structure in the overall period and the period before the Covid-19 pandemic, but enhances the effect of capital structure on financial performance in the period before the Covid-19 pandemic.